MODEL COMPETENCY BASED ASSESSMENT PADA PENGEMBANGAN JOB PERFORMANCE PUBLIC AREA DI HOUSEKEEPING DEPARTMENT - Jubaedah, Yoyoh; Rohaeni, Neni; Rinekasari, Nenden Rani; Rohmah, Iis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2018)
The purpose of this research is to apply a competency-based assessment model on the job performance of Public Area at Housekeeping Department. The scope of the study produced 2 targets in housekeeping department: 1) competency based assessmen model on the job performance of public area; 2) assessment tool on job performance of public area. This study was used a descriptive method with three stages of development study. First is a preliminary study, second stage is development model, and finally is validation test of the model. The research subject was teacher of public area subject matter, and employees of housekeeping department. Data was collected through interviews, observations, and expert judgment. Data was analyzed in accordance with the procedures and characteristic of the findings. It was used both the qualitative and quantitative data. The finding showed that competency-based assessment model on the job performance of public area in housekeeping department included the planning, the instrument and the process of assessment stages. The instrument consisted of the preparation, practices, and outcome of assessment stages. The conclusion is assessment tools on the public area practices using competency-based assessment is very appropriate to apply this competency-based assessment at senior vocational high school, especially for job performance on housekeeping department expertise. Abstrak Tujuan dari penelitian ini adalah untuk menerapkan model Competency Based Assessment pada pengembangan Job Performance Public Area di Housekeeping Department. Target khusus yang ingin dicapai dari penelitian ini adalah menghasilkan: (1) Model Competency Based Assessment pada pengembangan Job Performance Public Area di Housekeeping Department, (2) Alat Penilaian Job Performance Public Area di Housekeeping Department. Penelitian ini mengunakan metode deskriptif dengan pendekatan Research and Development. Studi pengembangan ini dilakukan dalam tiga tahap, meliputi: Tahap pertama merupakan tahap studi pendahuluan, Tahap kedua merupakan tahap pengembangan model dan Tahap ketiga merupakan tahap uji validasi model. Subjek penelitian terdiri dari guru pengampu mata pelajaran Public Area dan praktisi dari housekeeping depatment. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan expert judgement. Analisis data penelitian dilakukan sesuai dengan prosedur dan karakteristik dari temuan data penelitian; untuk data kuantitatif dianalisis secara kuantitatif dan untuk data kualitatif dianalisis secara kualitatif. Temuan penelitian berkaitan dengan Model Competency Based Assessment pada pengembangan Job Performance Public Area di Housekeeping Department meliputi tahap perencanaan penilaian, instrumen penilaian, dan pelaksanaan penilaian. Instrumen penilaian terdiri dari tahap persiapan praktik, proses praktik, dan hasil praktik. Dari temuan penelitian dan hasil validasi dapat disimpulkan bahwa Alat Penilaian praktik Public Area dengan menerapkan model Competency Based Assessment â€œsangat layakâ€ untuk diimplementasikan di SMK Akomodasi Perhotelan dan di Housekeeping Department pada saat melakukan penilaian terhadap Job Performance Public area. Kata Kunci : Model, Competency Based Assessment, Job Performance, Public Area, Housekeeping Department.